ALKALINE PROTEASE, AMYLASE AND CELLULASE ACTIVITIES OF YELLOW RASBORA, Rasbora lateristriataBlkr., AT DIFFERENT FEEDING LEVELS - Untung Susilo; Purnama Sukardi; Ridwan Affandi (Molekul, 2016)
Alkaline proteases, amylase and cellulase activities of digestive organ of yellow rasbora, Rasbora lateristriata Blkr., was evaluated with four different feeding levels of 0.34g protein+0.03g fiber, 1.01g protein+0.10g fiber, 1.69g protein+0.16g fiber and 2.36g protein+0.23g fiber/day/100 g fish biomass. A total of 280 fish with average body weight of 0.71±0.06g were used in this study. The results showed that the difference in the feeding levels resulted in a significant difference in trypsin and chymotrypsin  activities (P <. 05), but not for amylase and cellulase activities (P > .05). In conclusion, protein digestion capacity increased, but not to the digestion of starch and fiber in response to different feeding levels and the optimal feeding level for yellow rasbora was 1,01g protein+0,10g fiber/day/100 g fish biomass.